The determinants of banking regulation in the MENA region - Hanene Ksiaa; Mohamed Imen Gallali (The Journal of Entrepreneurial Finance (JEF), 2022)
Theoretical foundations in banks' response to capital settlement suggest that the systems proposed by Basel are not sound. It is conceivable that regulators will consider alternative approaches to enhance the safety and soundness of the banking system. The regulation includes several decrees and ratios; the areas of interest encompassing the areas are subject to principal component analysis (PCA).The paper aims to present a regulatory framework based on balance sheet ratios, such as Capital requirements (equity ratio; Tier 1 ratio; Total Equity/Net Loans; Total Equity/Deposits); for liquidity needs (liquidity/deposits; liquidity/total assets; liquidity/deposits and loans, and net loans/total assets); for leverage requirements (total liabilities/total assets; total assets/equity; and total liabilities/equity); also banking restriction index; Official supervision index; Private surveillance index, finally global index of regulations and supervision. Besides, it performs a PCA analysis on a set of 13 financial ratios to exploit and compare the financial characteristics of 239 banks (175 Conventional and 64 Islamic commercial banks) in the MENA region over a 2004-2015 period. This gives the main indices EXIGCP, EXIGLIQ, LEVCP, and LEVP.
Keywords: G18; G21; G28; C38; 650; Banks; Regulation; Basel I; II; III; Principal Component Analysis; MENA